BIM 5D QUANTITY TAKE-OFF: DEVIATION AND ERROR SOURCE ANALYSIS IN REINFORCED CONCRETE - Lautan Wijaya Nusantara, Johan; Cahyono, Guntur Tri; Wusqo, Urwatul; Faveryan, Irkhas Bayu; Nisa, Mitsaq Addina; Tiyani, Lilis; Maryani, Desi (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2026)
Accurate quantity take-off is essential for reliable construction cost estimation, particularly in reinforced concrete works, which involve complex and error-prone calculations. This study evaluates the accuracy of BIM 5D-based quantity take-off and examines cost deviations compared to conventional contractor estimations. A three-story dormitory building was modeled using BIM 5D (Cubicost), and the results were validated against manual analytical calculations. The validation shows strong agreement, with a maximum deviation of 0.75% and a high linear correlation across concrete, reinforcement, and formwork quantities. A comparative analysis with the contractor’s Bill of Quantity reveals a cost difference of approximately 3.4%, with the contractor’s estimate being higher. This deviation is primarily attributed to simplifications in conventional methods, including double counting at element interfaces, generalized reinforcement detailing, and the inclusion of material allowances. In contrast, BIM 5D enables a more integrated and precise estimation by accounting for element interactions and optimizing reinforcement configurations. However, the results also highlight that BIM-based estimation is sensitive to modeling assumptions and parameter settings. Therefore, aligning BIM models with actual construction practices is essential to ensure reliable and applicable results. Overall, this study demonstrates the potential of BIM 5D to enhance the accuracy, consistency, and transparency of construction cost estimation.